2007
DOI: 10.1016/j.amjhyper.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor Gene Polymorphisms and Risk of Ischemic Stroke

Abstract: Our data suggest that the Glu27 allelic variant of the beta2-AR gene may be a determinant of ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
1
20
1
1
Order By: Relevance
“…This seems counter-intuitive at first glance, given that the derived allele shows signatures of positive selection based on human-chimp-comparisons (Bochdanovits et al 2009), and given the various positive associations that have been found for the derived allele with autism (Cheslack-Postava et al 2007) and health-related phenotypes (Gjesing et al 2007;Pinelli et al 2006;Stanzione et al 2007). On second sight, however, such antagonistic effects are what should be expected for derived alleles that are still variable today, despite positive selection acting on them recurrently, since the human and chimpanzee lineages split 6-7 million years ago (Harris 2008).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This seems counter-intuitive at first glance, given that the derived allele shows signatures of positive selection based on human-chimp-comparisons (Bochdanovits et al 2009), and given the various positive associations that have been found for the derived allele with autism (Cheslack-Postava et al 2007) and health-related phenotypes (Gjesing et al 2007;Pinelli et al 2006;Stanzione et al 2007). On second sight, however, such antagonistic effects are what should be expected for derived alleles that are still variable today, despite positive selection acting on them recurrently, since the human and chimpanzee lineages split 6-7 million years ago (Harris 2008).…”
Section: Discussionmentioning
confidence: 92%
“…The ancestral G allele of the rs1042714 SNP has been associated with increased risk of ischemic stroke (Stanzione et al 2007), high systolic blood pressure (Gjesing et al 2007), and type-2 diabetes (Pinelli et al 2006, but see Gjesing et al 2007). However, all effects we reported here remained virtually unchanged after controlling for selfreported histories of these three conditions or of cardiovascular diseases (only 13 subjects (8%) had diabetes and six (3.7%) ever had a stroke in this generally healthy sample).…”
Section: Confounding Effects Of Health Historymentioning
confidence: 98%
“…Contrasting effects of the ADRB2 Gln27Glu polymorphism have been shown in several cardiovascular diseases. Stanzione et al (33), for instance, showed that Glu27 allele carriers had an increased risk of stroke. In other study, Liggett et al (21) found no relationship between the Arg16Gly, Gln27Glu, and Thr164Ile polymorphisms of the ADRB2 gene and chronic heart failure (CHF).…”
Section: Resultsmentioning
confidence: 98%
“…Los principales sistemas fisiológicos que se encuentran involucrados en el control de la presión arterial son el sistema renina-angiotensina-aldosterona, el endotelio vascular, la transducción de señales por vía del sistema nervioso y las proteínas del citoesqueleto, que se encargan del mantenimiento del flujo sanguíneo (presión sanguínea y volumen de fluidos extracelulares en el cuerpo), mediación de reacciones de vasodilatación-vasoconstricción y la regulación de la concentración de sales (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
unclassified